PVA/ZnO-Modified Bacterial Cellulose Acetate Membranes from Pineapple Peel Waste with Improved Thermal Stability, Antibacterial, and Filtration Performance - Uun Yanuhar; Heru Suryanto; Joseph Selvi Binoj; Leong‑Seng Lim; Arumugam Kumaravel; Aminnudin Aminnudin; Fajar Nusantara; Defa Rizqi Machfuda; Komarudin Komarudin; Aulia Surya Ramadhan (Journal of Multidisciplinary Applied Natural Science, 2026)
The purpose of this work is to create and assess bacterial cellulose acetate (BCA) membranes reinforced with zinc oxide (ZnO) nanoparticles and mixed with polyvinyl alcohol (PVA). BCA membranes were made from pineapple peel biowaste and they contain 0.25 wt.% ZnO and PVA at 2.5 wt.% and 5.0 wt.%. Fourier-transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction (XRD) were used to observe the properties of membrane structure. Thermogravimetric analysis was used to examine the developed membrane's thermal degradation. Additionally, the filtration capabilities and antibacterial activity were examined. Furthermore, the membrane's morphology demonstrates that the addition of PVA results in denser surfaces, and ZnO was distributed without substantially changing the fiber's morphology. Similarly, the XRD analysis shows that as the PVA content increases, the crystallinity index decreases and the crystallite size slightly increases. Moreover, the thermal analysis demonstrated that PVA improves membrane stability by reducing the rate of mass loss. The PVA has a minor impact on antibacterial activity against Staphylococcus aureus and Escherichia coli. However, it appears that the ZnO content in the membrane was the source of the antibacterial activity. Besides, the brackish water filtration test revealed that the addition of PVA at 2.5 wt.% and 5.0 wt.%, respectively, enhanced the efficacy of bacterial filtration by 17.9 and 10.7 times. These results demonstrate that PVA/ZnO-modified BCA membranes are viable, environmentally friendly options for sustainable aquaculture and water filtration systems.